2011
DOI: 10.1111/j.1540-8175.2011.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Left Atrial Function in Patients with Coronary Artery Disease by Two‐Dimensional Strain and Strain Rate Imaging

Abstract: LA diastolic dysfunction occurs prior to LA systolic dysfunction in CAD patients, and LAs SR is the most accurate index in identifying patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 27 publications
5
35
1
Order By: Relevance
“…We used conventional echocardiography and STE. STE is an imaging technique, in which ultrasound speckles within the image are tracked, and strain is derived from the displacement of speckles relative to each other 31. This new modality enables accurate and reliable measurements of both global and regional myocardial strain and strain rates without the confounding effects of angle dependency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We used conventional echocardiography and STE. STE is an imaging technique, in which ultrasound speckles within the image are tracked, and strain is derived from the displacement of speckles relative to each other 31. This new modality enables accurate and reliable measurements of both global and regional myocardial strain and strain rates without the confounding effects of angle dependency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial contractile dysfunction appears early in ischemic heart disease (IHD), irrespective of previous myocardial infarction, co-existing systolic dysfunction, or severity of diastolic dysfunction [26], [9], [8]. Yu et al found that the peak regional atrial contraction velocities at atrial systole (V Aa ) measured at mid-level of the inter-atrial septum and the lateral LA in the apical four chamber view were drastically reduced in patients with IHD when compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…LA contractile dysfunction was, however, demonstrable in patients with coronary artery disease (CAD) even when the LV systolic function was preserved and LA was not enlarged [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that LA myocardial deformation parameters might be reduced before the atrial volume was changed [24], [25]. Furthermore, it is recommended to use several, rather than single doppler echocardiographic technique for the accurate assessment of cardiac diastolic function [26].…”
Section: Discussionmentioning
confidence: 99%